Kindergarten cop 2 [videorecording (DVD)] - Monaco, Jake (Universal Studios Home Entertainment, 2016)
To recover stolen data in a progressive school, the FBI's toughest agent must go undercover on his most difficult assignment yet: teaching a class full of liberal kindergarteners.